A PERSPECTIVA DA EDUCAÇÃO AMBIENTAL CRÍTICA FRENTE AO IMINENTE COLAPSO SOCIOAMBIENTAL GLOBAL (Publicatio UEPG: Ciências Sociais Aplicadas, 2021)
In view of the emergence of the environmental crisis and the imminent global socio-environmental collapse, the creation of another, new or more appropriate, relationship between human beings, society and nature is urgent. The idealized way to face the crisis and resist the collapse is the search to overcome the model of capitalist society based on anthropocentric ethics. Environmental education from a critical perspective emanates as a possibility to follow this path, due to the political-ideological positioning of social transformation. This theoretical essay, characterized as a literature review of the narrative type, aims to discuss and reflect on critical environmental education as a training process that seeks to: face the causes and consequences of the socio-environmental crisis; resist the imminent global socio-environmental collapse; overcome the dichotomous and hegemonic patterns in force; transform the historically constituted relationships between human beings, society and nature; and constitute another, new or more appropriate, way of living in society.